Mothers' Knowledge About Toddler Growth and Development in Posyandu Sejahtera 1 Benyo Sendangsari Hamlet - Dila Istiqomah Lisa; Wiwin Hindriyawati; Teguh Budi Prasetyo (Journal of Education Technology Information Social Sciences and Health, 2024)
Suboptimal growth and development in children will have an impact on the incidence of growth and development disorders in children under five years of age and can cause the risk of stunting. The results of Riskedes (2018) show that 35.7% of children in Indonesia experience developmental growth disorders and are classified as high public health problems. The occurrence of non-optimal child growth and development is due to a lack of knowledge in the family, especially mothers. Maternal knowledge will determine attitudes and behaviors in providing nutrition, affection, and the frequency of stimulation given to their children. The purpose of this study was to determine the knowledge of mothers about the growth and development of toddlers at Posyandu Sejahtera 1 Benyo Sendangsari Hamlet. This research is a mixed methods research, which is a research step by combining two forms of approaches in research, namely qualitative and quantitative. The sampling technique in this study used 2 techniques, namely total sampling and purposive sampling techniques. Data analysis in this study used univariate and descriptive analysis. The results of the study based on the level of knowledge of mothers about toddler growth and development were categorized as good knowledge as many as 15 respondents (50.0%), sufficient knowledge as many as 13 respondents (43.3%) and less knowledge as many as 2 respondents (6.7%). The results of the interview can be concluded that the informants have been and often get information from health workers and get information from social media and brochures, in the nutritional status of toddler growth is sufficient, meaning that mothers of toddlers already understand and know about toddler growth and development knowledge.